INDIVIDUALIZATION OF TRAINING OF SEWING PROFESSIONALS PROFILE IN THE CONTEXT OF VOCATIONAL EDUCATION DEVELOPMENT (Pedagogy of Higher and Secondary Education, 2008)
Researched the individualization of sewing industry workers’ studying in the context of vocational education tendency of development in present-day. Determined the ways of solving the problem of sewing industry workers * studying individualization.